Swine farms' waste destination of northwestern and southwestern regions of Paraná - Andreazzi, Márcia Aparecida; Santos, José Maurício Gonçalves dos; Lazaretti, Rhubia Maria Jorge (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The constant increase in world's population is associated with the necessity to intensify foods' production, whether from plants or from animals. However, this augment the generation of waste in chains' production. Forewarn swine's' producers to enhance production whital reduce harming the environment becomes necessary, since swine's farm is an agricultural activity that causes substantial impacts to the environment. This study aims was to characterize, in farms from destination of northwestern and southwestern regions of Paraná, swine farms' systems and the disposal of the waste due to these practices. For data collection, visits were made "in loco" in order to collect the data: production's system, animals' number, mortality rate, disposal of carcass from dead animals and of waste. From this survey, it was concluded that carcasses' allocation of dead animals includes mainly composting and septic tank, as well as the waste is sent, mostly, to treatment's ponds. However, the farms that participate in integration'sprojects resort the biodigester and invest in minimizing the environmental impact of the swine's creation. These farms persue, with the use of biodigesters, frame swine's creation in the environmental sustainability, economic and social's triad